Have trading rule profits in the currency markets declined over time? - Olson, Dennis (Journal of Banking & Finance, 2004)
Previous studies have reported mixed results regarding the success of technical trading rules in currency markets. Abnormal returns were observed in many studies using data up to the mid 1980s, while more recent studies generally report less success for technical trading rules. This paper tests whether moving average trading rule profits have declined over the period from 1971 to 2000. If so, previous profits may represent a temporary inefficiency that has since been eliminated in the currency markets. The hypothesis is tested using 18 exchange rate series over a longer time period than in previous studies. Rules are optimized for successive 5-year in-sample periods from 1971 to 1995 and tested over subsequent 5-year out-of-sample periods. Results show that risk-adjusted trading rule profits have declined over time-from an average of over 3% in the late 1970s and early 1980s to about zero in the 1990s. Thus, market inefficiencies reported in previous studies may have been only temporary inefficiencies.